Network Governance In Handling Problems Of Asylum Seekers In Pekanbaru City - Zainal Zainal; Fajar Muhammad (UIR Press, 2021)
The increasing arrival and presence of asylum seekers in Pekanbaru City has presented its own problems that are feared and have an impact in the fields of ideology, politics, economy, socio-culture, national security, and immigration vulnerability. This study aims to determine network governance in dealing with the problems of asylum seekers in Pekanbaru City. This study uses a qualitative method, which is a study that uses humans as research instruments that are adapted to the situation and conditions in the field. The results of the study show that networking governance between stakeholder institutions has not been going well so that there are still many immigrants who violate and conflict with existing regulatory provisions. The conclusion of this research is that in terms of involvement, commitment, roles, and mechanisms, the three institutions have been well implemented. The research suggestion is that all stakeholders are expected to establish cooperative relationships and coordinate with the Pekanbaru City Government, the police and other parties involved in monitoring the presence of asylum seekers or illegal immigrants in Pekanbaru.